ASSESSMENT OF DIFFERENTIATION STRATEGY ON THE PERFORMANCE OF THE SUGAR INDUSTRY IN WESTERN KENYA - ONDERE, JUSTUS; SANGORO, MR. OSCAR; AKETCH, MR. ROMAN; OTUYA, DR. WILLIS (IJRDO - Journal of Business Management, 2016)
The uncompetitiveness of the sugar industry in Kenya necessitated this study to be carried out. The purpose of the study was to assess the application of the differentiation strategy on the performance of the sugar industry in Western Kenya. The study adopted a descriptive survey design to collect data and was carried out in western Kenya. It targeted employees of Mumias, Nzoia, West Kenya and Butali sugar companies. Questionnaires, interview schedules and observation checklists were used as research instruments. Target population was 1851 employees comprising the management and non management staff making a sample size of 179 employees. Purposive sampling technique was adopted to select employees to participate in the study. To determine the validity of the instruments, they were developed and presented to research experts and my supervisors at the university to establish whether they measured what they intended to measure and to modify them accordingly. Test-re-test method was used where the same instruments were administered more than once to the same people under identical conditions then the performance was compared. For reliability of the results, piloting was carried out at Chemelil and Muhoronii sugar firms before the actual field study. Data was analyzed using both descriptive and inferential statistics after collection. Mumias Sugar Company was found to be aggressive as compared to the three remaining companies. Thus the company stands to gain in terms of corporate image and reputation due to high promotion activities. Lastly, four challenges were identified facing sugar industry performance in western Kenya. These were government policy and politics in the management of the firms, liberalization which has led to importation of cheap sugar from COMESA member countries and Brazil